Sol-Gel derived particles, Low-Sintering temperature ceramic, Thin and thick films of barium zirconate titanate system - Nawal Binhayeeniyi (Prince of Songkla University Faculty of Science (Physics), 2013)
Thesis (Ph.D., Physics)--Prince of Songkla University, 2011